Finns Clostridium difficile i köttprodukter i Sverige? : en pilotstudie - Karlsson, Frida (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2009)
Clostridium difficile is a grampositive, anaerobe bacteria with a spore-forming ability. The bacteria is present in the environment, can be isolated from animals and is common in hospitals, where it is a known cause of severe diarrhoea in compromised patients. Lately scientists have been discussing whether Cl. difficile could be a new food-borne pathogen. The bacteria has been isolated from food-producing animals and from meat products.